The Relationship Between Dietary Protein Intake Restriction and Mortality Risk in Stage V Chronic Kidney Disease Patients With Haemodialysis : Literature Review - M. Agung Prasetya Adnyana Yoga; Reni Zuraida; Dian Isti Angraini (CV. AFDIFAL MAJU BERKAH, 2025)
Chronic Kidney Disease (CKD) is a condition in which kidney function progressively declines and irreversibly diminishes so that the kidneys are unable to maintain metabolic, fluid and electrolyte balance resulting in uremia and azotemia. One of the kidney replacement therapies in stage 5 of CKD is by hemodialysis procedure. There are 5 – 8 g/dialysis amino acids losses during the hemodialysis (HD) procedured , if protein loss is not replaced with adequate dietary protein intake it will certainly affect malnutrition which can increase the risk of mortality. Inadequate protein intake is associated with protein energy wasting. However, the associated impact of protein intake on mortality remains unclear. Literature review was conducted to identify the effect of protein intake restriction on mortality risk in CKD patients undergoing hemodialysis. Articles were searched through NCBI (The National Center for Biotechnology Information), PubMed/Medline and Science Direct. Prisma Method was used to describe the process of selecting journals in a structured manner so that valid journals are obtained for analysis in this study. The results showed that appropriate management of protein intake for patients undergoing haemodialysis is necessary to prevent malnutrition, high protein intake can increase phosphorus and potassium levels and risk metabolic acidosis, and extensive restriction can lead to malnutrition and death with the hazard ratio 1.33. It is recommended that protein intake in CKD patients undergoing hemodialysis be in the range of 1.0 - 1.2 g/kg/day.